Stable Expression of hom-1-thrB in Corynebacterium glutamicum and Its Effect on the Carbon Flux to Threonine and Related Amino Acids - Reinscheid, Dieter J. (1994)
The hom-1-thrB operon encodes homoserine dehydrogenase resistant to feedback inhibition by L-threonine and homoserine kinase. Stable expression of this operon has not yet been attained in different Corynebacterium glutamicum strains. We studied the use of chromosomal integration and of a low-copy-number vector for moderate expression of the hom-1-thrB operon to enable an analysis of the physiological consequences of its expression in C. glutamicum. Strains carrying one, two, or three copies of hom-1-thrB were obtained. They showed proportionally increased enzyme activity of feedback-resistant homoserine dehydrogenase and of homoserine kinase. This phenotype was stably maintained in all recombinants for more than 70 generations. In a lysine-producing C. glutamicum strain which does not produce any threonine, expression of one copy of hom-1-thrB resulted in the secretion of 39 mM threonine. Additional copies resulted in a higher, although not proportional, accumulation of threonine (up to 69 mM). This indicates further limitations of threonine production. As the copy number of hom-1-thrB increased, increasing amounts of homoserine (up to 23 mM) and isoleucine (up to 34 mM) were secreted. Determination of the cytosolic concentration of the respective amino acids revealed an increase of intracellular threonine from 9 to 100 mM and of intracellular homoserine from 4 to 74 mM as the copy number of hom-1-thrB increased. These results suggest that threonine production with C. glutamicum is limited by the efflux system for this amino acid. Furthermore, the results show the successful use of moderate and stable hom-1-thrB expression for directing the carbon flux from aspartate to threonine.